2011
DOI: 10.1063/1.3562143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of excitation wavelength on dynamics of laser-produced tin plasma

Abstract: We investigated the effect of the excitation wavelength on the density evolution of laser-produced tin plasmas, both experimentally and numerically. For producing plasmas, Sn targets were excited with either 10.6 lm CO 2 laser or 1.06 lm Nd:yttrium aluminum garnet laser; both are considered to be potential excitation lasers for extreme ultraviolet lithography laser-produced plasma light sources. The electron density of the plasma during the isothermal expansion regime was estimated using an interferometric tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…Instead, along with collisional excitation of the plume, ambient air also affects the plasma chemistry through oxide and other reactive species formation [32]. temperature can reach > 10 eV [34,35]. According to Singh et al [36], assuming adiabatic and spherical expansion of the plume, both these parameters decay by ~ 1/r 3 with space where r is the radius of the plume.…”
Section: Resultsmentioning
confidence: 98%
“…Instead, along with collisional excitation of the plume, ambient air also affects the plasma chemistry through oxide and other reactive species formation [32]. temperature can reach > 10 eV [34,35]. According to Singh et al [36], assuming adiabatic and spherical expansion of the plume, both these parameters decay by ~ 1/r 3 with space where r is the radius of the plume.…”
Section: Resultsmentioning
confidence: 98%
“…where Z is the average charge, C; n i is the Ion number density, cm -3 ; v 0 is the incident frequency, Hz; T i is the particle temperature, K; and Assuming that one electron is excited from each atom in local thermal equilibrium, then the free electron concentration can be obtained using the Saha equation: In the duration and end phases of the laser pulses, the generated plasma motion generally can be divided into two processes: isothermal expansion and adiabatic expansion [15]. In laser ablation, only the process related to the shielding effect caused by laser adsorption (i.e., isothermal expansion) was studied.…”
Section: The Plasma Shielding Effectmentioning
confidence: 99%
“…Theoretical and experimental studies [20,[30][31][32] have shown that the~10−μm wavelength generated by CO 2 lasers is favourable for LPP EUV source over the~1−μm wave− length delivered by solid−state lasers in terms of higher CE and reduced debris production [23,24]. An optimal times− cale for an energy coupling from the laser field to the plasma, dictated by the expansion dynamics, was found to be a few nanoseconds for the Nd:YAG lasers [33] and around ten nanoseconds for the CO 2 lasers [31].…”
Section: Pulse Format Requirements For 135 Nm Lpp Euv Sourcementioning
confidence: 99%